Biology : a guide to the natural world - Krogh, David, 1949- (Upper Saddle River, New Jersey : Prentice-Hall, 2000)
An encyclopedia of basic definitions for youngsters in the primary grades.
Keywords: BIOLOGIA -- ENSEÑANZA -- GUIAS; BIOLOGIA EVOLUTIVA